Model Prediksi Tindakan Pencegahan Rabies untuk Menegakkan Sistem Kewaspadaan Dini (SKD) pada SMA di Kota Kendari Tahun 2025 - Annisya Syarifuddin; La Ode Muhamad Sety; Mubarak Mubarak (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Rabies is a deadly disease transmitted through animal bites, especially dogs, and remains a serious threat in Indonesia. As of April 2023, more than 31,000 bite cases have been recorded, with Southeast Sulawesi being the region with the highest number of cases. In Kendari City, data show that bite cases have fluctuated since 2018. Research Objective: To develop a prediction model for rabies prevention measures to support an early warning sistem (EWS) among high school students in Kendari City. Research Methods: A cross-sectional quantitative study involving 350 students from three sub-districts (Baruga, Poasia, and Kadia). Independent variables included knowledge, attitudes, and beliefs, while the dependent variable was rabies prevention measures. Data were collected in February 2025 through a hybrid/online questionnaire. Research Results: Knowledge, attitudes, and beliefs have a significant effect on rabies prevention measures among high school students in Kendari City. Knowledge was the most dominant factor. Students with good knowledge were 8.7 times more likely to practice rabies prevention. If the three variables were at a low level, the probability of rabies prevention actions among students was 14.4%, but it increased significantly to 95.6% when all three variables were at a high level. Research Conclusion: There is a significant influence of knowledge, attitudes, and beliefs on rabies prevention behavior to support the early warning sistem (EWS) among high school students in Kendari City in 2025. The probability of engaging in preventive behavior is 14.4% when all three variables are at a low level, but it increases significantly to 95.6% when all variables are at a high level. Knowledge contributes the most, while attitudes and beliefs synergistically strengthen the overall effect.